Metal - Raphael, Max.; Hickey, Matthew P.; Nash, Bruce M.; Actuality Productions; Arts and Entertainment Network; New Video Group; History Channel (Television network) ([New York] : A & E Television Networks, 2003)
Trace the development of the ubiquitous materials that literally support the modern world. Includes metals such as copper, bronze, tin, gold, iron, steel, aluminum, and the processes used to produce them. The journey begins with the ancient world, when the techniques of extracting and shaping bronze and then iron into tools and weapons were developed. The video continues into the 21st century with new metals/materials being designed at the molecular level. It also looks at the many ways that metal is woven into the fabric of our society.
Writer/producer, Matthew P. Hickey ; producer, Bruce Nash.
Narrator, Max Raphael.
MPAA rating: Not rated.
DVD.
Keywords: Metals; Metallurgy